Full solar-spectral reflectance of ZnO QDs/SiO2 composite pigment for thermal control coating. (February 2022) - Chen, He; Li, Peng; Zhou, Haitao; Zhang, Wei; Cong, Lujia; Ma, Jiangang
Highlights: ZnO QDs/SiO2 composite pigment with high reflectance in the range of 200–2600 nm were successfully synthesized by sol-gel method and post annealing. TEM measurements indicate that ZnO QDs with the size of several nanometers had been distributed uniformly in SiO2 matrix in the composite pigment. Exciton emission from ZnO QDs was observed in PL spectra and the emission energy shifted to low energy side with the increasing size of ZnO QDs, which agrees with the quantum confinement effect. According to the data fitting of the temperature dependent PL spectra, the exciton binding energy of the ZnO quantum dots in the composite pigment can reach 63 meV. Abstract: Thermal control coatings play an important role in the long-term operation of spacecrafts. The next generation of outer space technology demands thermal control coatings for high reflectivity not only in the visible and infrared but also in the ultraviolet spectral range. In this paper, ZnO quantum dots (QDs) and SiO2 composite pigments were prepared by the rapid injection sol-gel method and subsequent sintering. A high reflectance above 60% in the full solar-spectral range of 200–2600 nm was reached with the composite pigments at an optimized sintering temperature. The structural and optical properties of the ZnO QDs/SiO2 composite pigments with respect to the sintering temperature are studied using X-ray powder diffraction, Scanning and Transmission electron microscopy, Raman scattering, Photoluminescence, Fourier-transform infrared spectroscopy. The mechanism enabling the full solar spectral reflectance is discussed in terms of the quantum confinement effect and the Kubelka–Munk theorem. Graphical abstract: Image, graphical abstract